Special Theme: Project Management in E-Science: Challenges and Opportunities - Spencer, Dimitrina; Zimmerman, Ann; Abramson, David (Computer supported cooperative work, 2011)
In this introduction to the special theme: Project Management in e-Science: Challenges and Opportunities, we argue that the role of project management and different forms of leadership and facilitation can influence significantly the nature of cooperation and its outcomes and deserves further research attention. The quality of social interactions such as communication, cooperation, and coordination, have emerged as key factors in developing and deploying e-science infrastructures and applications supporting large-scale and distributed collaborative scientific research. If software is seen to embody the relational web within which it evolves, and if the processes of software design, development and deployment are seen as ongoing transformations of this dynamic web of relationships between technology, people and environment, the role of managers becomes crucial: it is their responsibility to balance and facilitate the dynamics of these relationships.